Accelerating the clinical development of protein-based vaccines for malaria by efficient purification using a four amino acid C-terminal 'C-tag'. Issue 7 (June 2017) - Jin, Jing; Hjerrild, Kathryn A.; Silk, Sarah E.; Brown, Rebecca E.; Labbé, Geneviève M.; Marshall, Jennifer M.; Wright, Katherine E.; Bezemer, Sandra; Clemmensen, Stine B.; Biswas, Sumi; Li, Yuanyuan; El-Turabi, Aadil; et al.
Graphical abstract: Highlights: Fusion of a four amino acid 'C-tag' allows purification of a PfRH5 malaria vaccine. Overall process yield of 40–45% and very high product purity (>99%) was achieved. His6-tagged and C-tagged PfRH5 are conformational and bind to basigin. C-tag will facilitate the clinical translation of difficult-to-produce antigens. Abstract: Development of bespoke biomanufacturing processes remains a critical bottleneck for translational studies, in particular when modest quantities of a novel product are required for proof-of-concept Phase I/II clinical trials. In these instances the ability to develop a biomanufacturing process quickly and relatively cheaply, without risk to product quality or safety, provides a great advantage by allowing new antigens or concepts in immunogen design to more rapidly enter human testing. These challenges with production and purification are particularly apparent when developing recombinant protein-based vaccines for difficult parasitic diseases, with Plasmodium falciparum malaria being a prime example. To that end, we have previously reported the expression of a novel protein vaccine for malaria using the ExpreS 2 Drosophila melanogaster Schneider 2 stable cell line system, however, a very low overall process yield (typically <5% recovery of hexa-histidine-tagged protein) meant the initial purification strategy was not suitable for scale-up and clinical biomanufacture of such a vaccine. Here we describe a newly available affinity purification method that was ideally suited to purification of the same protein which encodes the P. falciparum reticulocyte-binding protein homolog 5 – currently the leading antigen for assessment in next generation vaccines aiming to prevent red blood cell invasion by the blood-stage parasite. This purification system makes use of a C-terminal tag known as 'C-tag', composed of the four amino acids, glutamic acid – proline – glutamic acid – alanine (E-P-E-A), which is selectively purified on a CaptureSelect™ affinity resin coupled to a camelid single chain antibody, called NbSyn2. The C-terminal fusion of this short C-tag to P. falciparum reticulocyte-binding protein homolog 5 achieved >85% recovery and >70% purity in a single step purification directly from clarified, concentrated Schneider 2 cell supernatant under mild conditions. Biochemical and immunological analysis showed that the C-tagged and hexa-histidine-tagged P. falciparum reticulocyte-binding protein homolog 5 proteins are comparable. The C-tag technology has the potential to form the basis of a current good manufacturing practice-compliant platform, which could greatly improve the speed and ease with which novel protein-based products progress to clinical testing.